P298 Wall thickness ratio, a new magnetic resonance parameter, predicts the outcome of biological therapy in patients with ileal and ileocolonic Crohn's disease. (25th January 2019) - Balestrieri, P; Ribolsi, M; Tullio, A; Solida, E; Giordano, A; Cicala, M
Abstract: Background: Magnetic resonance enterography (MRE) is a non-invasive useful tool for assessing the transmural and extraintestinal lesions in Crohn's disease (CD). The absolute measure of transmural healing (TH) has been recently associated to improved long-term outcome in CD. However, a not negligible proportion of patients responding to biological therapy does not achieve TH. The aim was to identify a new MRE parameter assessing clinical outcome of biological therapy in patients with active ileal or ileocolonic CD. Methods: Consecutive patients with ileal or ileocolonic involvement, attending our IBD unit and scheduled for anti-TNF (Infliximab, Adalimumab) or anti-integrin therapy (Vedolizumab), were enrolled. All patients underwent MRE at baseline (T0) and after 1 year (T1). CRP and Harvey–Bradshaw index (HBI) were measured at T0, T1, and after 2 years of treatment (T2). Non-response to therapy was defined at T2 as: <3-point change in HBI (T0-T2), need for steroids, optimisation/change of treatment or surgery. TH, defined as wall thickness ≤3 mm without ulcers, oedema, enhancement and complications, was evaluated by MRE at T1. Wall thickness ratio (WTR) was calculated as wall thickness (mm) at T1/wall thickness at T0. Results: A total of 103 patients were enrolled: 56 were responders and 47 non-responders to biological therapy after 2 years of treatment. The median (±interquartile range) values of CRP and HBI were 15.0 mg/l [2–19] and 8.27 mg/l [6–10] at T0, 8.92 mg/l [1–4] and 4.95 [2–7.5] at T1 and 3.73 mg/l [1–4.5] and 4.54 mg/l [2–7.25] at T2. Overall, 16 out of 56 responders and 3 out of 47 non-responders achieved TH (28% and 6%, respectively, p < 0.01). Mean (±SD) WTR was 0.64 ± 0.23 in responders and 0.97 ± 0.26 in non-responders. According to the upper value of 95% confidence interval in non-responders, the WTR cut-off value of 0.87 was calculated. Therefore, 44 (78%) responders had a WTR < 0.87 and 20 (74%) non-responders had a WTR >0.87. In the group of responders, the proportion of patients with a WTR <0.87 was significantly higher than the proportion of patients achieving TH (78% vs. 28%, p < 0.01). The presence of a WTR <0.87 at T1 was significantly associated to a response to biological therapy at T2 (RR 3.6, 1.7–7.2) with a sensitivity of 74% and a specificity of 77%. Positive and negative predictive values were 71% and 80%, respectively. Conclusions: Wall thickness ratio appears to be a useful MRI variable as it discriminates responders to biological therapy, also in patients not achieving transmural healing. This novel variable accurately predicts a favourable response to biological therapy in CD patients and may be considered a useful parameter for monitoring patients during therapy.